Implementasi Mekanisme Khiyar Dalam Transaksi Jual Beli Di Pasar Raya Mekongga Kolaka - Hildayanti Syuaib; Suhrah Suhrah (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Pasar Raya Mekongga Kolaka is one of the markets in Kolaka Regency, which was founded in 1997 and inaugurated in 1998 with around 306 stalls divided into several blocks based on the main commodities, namely handicrafts, traders and daily necessities. Pasar Raya Mekongga Kolaka is a market for buying and selling transactions that sell various types of goods such as clothes, shoes, accessories, etc. with a bargaining system. The formulation of the problem in this study is how the implementation of khiyar and the khiyar mechanism in buying and selling transactions at Pasar Raya Mekongga Kolaka and the purpose of this study is to find out how the implementation of khiyar and the khiyar mechanism in buying and selling transactions at Pasar Raya Mekongga Kolaka. This research is a descriptive study, using a qualitative approach, and using the method of observation, interviews and documentation. The data collection techniques used are collecting data, simplifying data, and presenting data and discussing the methods that have been carried out. The results showed that Pasar Raya Mekongga Kolaka was a market for buying and selling transactions. Basically, the right of khiyar is applied in the practice of buying and selling, where the buyer can see directly the condition and quality of an item to be purchased. The khiyar that is applied by the buying and selling actors at Pasar Raya Mekongga Kolaka is khiyar majelis and khiyar requirements. Meanwhile, khiyar disgrace will be applied based on the initial agreement. The khiyar practice is implemented by traders at Pasar Raya Mekongga Kolaka. However, these traders do not know that the buying and selling practice is the practice of khiyar rights.